Apocuma (Cumacea: Bodotriidae): two new species from the West-Atlantic and a significant extension of the known distribution of this genus in the Atlantic Ocean - Roccatagliata, Daniel; Alberico, Natalia A.; Heard, Richard W. (Zootaxa, 2012)
Two new species of the genus Apocuma are described and illustrated: A. gerkenae n. sp. and Apocuma iorgui n. sp. Bothspecies were found off the coast of Brazil, but A. gerkenae was also recorded off the coasts of Georgia and Florida (bothon the Atlantic Ocean and in the Gulf of Mexico). Additionally, specimens of A. brasiliense collected off the coast of Riode Janeiro were examined. These three species differ mainly by (1) the presence / absence of a rudimentary exopod on thethird pereopod of the female, (2) the sculpture of the carapace, and (3) the uropod setation. The distribution of this genusin the Atlantic Ocean is substantially extended based mainly on an unpublished database compiled by the late Norman S. Jones.